(untitled) (Książnica Śląska, 2025)
The author discusses the presentation of the Silesian Uprisings in Szczepan Twardoch‘s prose. He mentions several heroes of the writer‘s novels to analyze their attitude towards events of the years 1919– 1921. Referring to those events, they seem, depending on their personal motives, either detached or deeply emotional. Therefore, the uprisings themselves become for some more a personal vengeance than a national spurt. It is clear, that for Twardoch the process of a protagonist‘s identity formation is far more significant than the subject of the uprisings.